Nesting Space Dynamics and Its Relationship with the Arribada of Olive Ridley Turtles at Gahirmatha Rookery, East Coast of India - Behera, Satyaranjan; Tripathy, Basudev; Sivakumar, K.; Choudhury, B. C.; Dutta, S. K.; Pandav, Bivash (Journal of herpetology, 2018)
Sea turtles use beaches that are suitable for the successful development of embryos. Heavy nesting on beaches may have detrimental effects on the survival of embryos as the result of the destruction of nests by conspecifics and physiological stress of the incubation substrate. We studied nesting space dynamics and the impacts of nesting Olive Ridley Sea Turtle (Lepidochelys olivacea) females on the hatching success in Gahirmatha rookery, along east coast of India. A reduction in beach area following a recent post super-cyclone presented an opportunity to test the hypothesis predicting that nest density would negatively affect nest and hatching success. The average calculated area was 475.4 cm2 for one nest cavity; therefore, the nest capacity of the beach was estimated to be 85,176 clutches. The high degree of nest overlap resulted in relatively low hatching success. We expect, however, that if erosion is arrested, the nesting space is likely to expand and thereby increase long-term hatching success at Gahirmatha.